2020
DOI: 10.1111/dth.14213
|View full text |Cite
|
Sign up to set email alerts
|

Is prenatal testosterone‐estrogen balance associated with psoriasis?

Abstract: The etiopathogenesis of psoriasis is not understood; however, psoriasis is affected by hormones, particularly the sex steroids. The second-to-fourth digit (2D:4D) ratio, which is an indicator of prenatal sex hormone balance, has been studied in various diseases that are affected by hormones. A total of 369 individuals comprising 172 patients with psoriasis and 197 healthy volunteers were included in the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…They also found negative correlation between PASI and estradiol levels. In our study, we think that the severity of ED's correlation with PASI may related to this [14,15].…”
Section: Discussionmentioning
confidence: 54%
“…They also found negative correlation between PASI and estradiol levels. In our study, we think that the severity of ED's correlation with PASI may related to this [14,15].…”
Section: Discussionmentioning
confidence: 54%
“…This hormonal imbalance was also reported by Tsilidis et al [22] and was associated with high C-reactive protein levels, a systemic marker of inflammation, which supports the proinflammatory theory. The relationship between sex hormones and the etiology of psoriasis studied by Ozir et al [23] found that estrogen and testosterone imbalance was an independent risk factor regarding psoriasis etiology in males. Some studies further mentioned a possible responsibility of sex hormones in reducing psoriasis severity, as supported by a marked reduction of C-reactive protein levels and improvement of psoriatic skin manifestations in 15 patients with psoriasis, and hypogonadism after treatment with a long-acting testosterone replacement therapy [24].…”
Section: Discussionmentioning
confidence: 99%
“…42 1960'lardan sonra sanata ve bedene yönelik algıların değişmesiyle; bedeni sanatsal bir araç olarak gören sanatçılar, onu sadece duygularını ifade etmek için kullanmamış, aynı zamanda bedenlerinin sınırlarını ve olanaklarını da keşfetmeye çalışmışlardır. 43 Yüzyıllardır iktidarların egemenliğinde olan bedenin kullanım şekli köklü bir değişime uğramış, beden sadece bir ressam tarafından çizilen veya şekillendirilen bir unsur değil, artık politik bir malzeme olarak kabul edilmiştir. 44 Ayrıca bu dönemde sanatçıların çalışmalarında kullanacakları anlatım yöntemleri ve teknikleri değişiklik göstermiş, sosyal ve siyasal bir gösterge olarak beden, başka bir varlığa dönüşerek sanatın nesnesi olmuştur.…”
Section: Sanatta Beden'in Kullanımıunclassified